Early Upper Paleolithic cultural variability in the Southern Levant: New evidence from Nahal Rahaf 2 Rockshelter, Judean Desert, Israel. Issue 178 (May 2023) - Shemer, Maayan; Boaretto, Elisabetta; Greenbaum, Noam; Bar-Yosef Mayer, Daniella E.; Tejero, Jose-Miguel; Langgut, Dafna; Gnezdilov, Dariya Lokshin; Barzilai, Omry; Marder, Ofer; Marom, Nimrod
Abstract: The Levantine Early Upper Paleolithic (ca. 45–30 ka) has been a focus of research because of its unique position as a conduit of human, flora, and fauna species between Africa and Eurasia. Studies have mainly focused on the Early Ahmarian and Levantine Aurignacian, two entities, the former endemic and the latter foreign, which are considered to have coinhabited the region during that period. However, other cultural entities, such as the Atlitian in the Mediterranean region and the Arkov-Divshon in the arid regions of the southern Levant received less attention, and accordingly, suffer from broad definitions and chronological insecurity. These cultures hold potential insights regarding nuanced adaptations, reciprocal influences, and diachronic assimilation processes. The recently discovered site of Nahal Rahaf 2 Rockshelter in the Judean Desert provides integral information on one of these entities—the Arkov-Divshon. Two excavation seasons revealed a sequence of archaeological layers, with lithic assemblages in which laterally carinated items were prominent. Alongside rich faunal assemblages, other components of the material culture include perforated marine shells and bone tools, marking the first association of these elements with Arkov-Divshon and implying some degree of contact with the Mediterranean regions of the Levant. Good preservation of organic materials allowed radiocarbon dating of the human occupation at the site to ca. 37.5–34.0 ka cal BP, indicating chronological overlap with the Levantine Aurignacian, and possibly also with the latest phases of the Early Ahmarian. Thus, challenging the validity of the widely accepted 'Two Tradition' Model of the Levantine Upper Paleolithic. Lithic analyses suggest the use of one main reduction sequence and the primary production of bladelets from carinated items. Faunal remains suggest targeted hunting of ibex and gazelle. Botanical remains and sedimentary analyses suggest roughly similar environmental conditions, with a possible woodier environment in the surroundings of the site.